Quantification de la charge d`entraînement imposée au footballeur professionnel en phase de réhabilitation athlétique post-blessure - Ben Belgith, A.; Ahmaidi, S.; Maille, P.; Noirez, P.; Desgorces, F. D. (Science & Sports, 2012)
The purpose of this study is to compare training load quantification methods "Work-Endurance-Recovery", "session-CR10" and "Training impulse" during a period of post-injury physical rehabilitation in professional soccer players. Methods: Eleven young soccer players injured participated in the study. This period of physical rehabilitation is composed of sessions of muscle conditioning, proprioception and individual work with ball. For all training sessions, Work-Endurance-Recovery training loads are not related to session-CR10 (P = 0.11). These two types of training loads result in significant correlations for proprioception and ball sessions (R2 = 0.60). In addition, significant correlation coefficients appear between TRIMPs and WER training loads (R2 = 0.62), and between TRIMPs (only calculated for proprioception and ball sessions) and session-CR10 (R2 = 0.66). Quantification of muscle conditioning sessions differs between Work-Endurance-Recovery and session-CR10 methods. These differences are due to the fact that the increase in exercise intensity associated with unchanged volume results in decreased effort perception. The particular context of muscular conditioning after injury underlines the limits of session-CR10 quantification method used during the first phase of a physical rehabilitation period. The WER method seems useable for all phases of physical rehabilitation. Our study underlines the feasibility of training load quantification for physical rehabilitation exercises after injuries that could allow to improve such exercises programs.